Crossing boundaries : using the theory of planned behaviour to explain intention to mix socially with members of other race groups. - Kurian, Hazel Claire (My University, 2009)
The aim of this research study is to assess the ability of the Theory of Planned Behaviour (TpB) to explain people’s intentions to interact interracially on a social level. It aims to understand the influence of students’ attitudes, perceptions of social norms and efficacy on these intentions. A questionnaire survey was administered to 226 students (37% White, 31% Black African, 27% Asian and 4% Coloured). The questionnaire was based on the standard format of the Theory of Planned Behaviour (Ajzen, 1991). The TpB model explained 35% of the variability in intention, providing support for its predictive power. The attitude, subjective norm and perceived behavioural control components of the model had good predictive ability demonstrating the usefulness of the model as a means to explain and predict intention to mix interracially. The results indicated that attitudes to mixing was the most powerful predictor of intention to mix inter-racially followed by perceived ability to effect this behaviour. Perception of social norms, while also statistically significant, was the least important factor. The findings suggest that the major obstacles to inter-racial interaction are intergroup attitudes and perceived inability to make such contacts.
Keywords: Boundaries; Planned behaviour; Mix socially; Race groups